Cap'n Eri - Lincoln, Joseph Crosby, 1870-1944 (Salt Lake City, UT : Project Gutenberg, 2006)
"Cap'n Eri" by Joseph Crosby Lincoln is a novel likely written in the early 20th century. The story follows Captain Eri, Captain Jerry, and Captain Perez, three retired sea captains who find themselves navigating the challenges of domestic life, including the unexpected prospect of marriage, as they seek a housekeeper to manage their disheveled household. The humorous interactions among these characters reveal their unique personalities and perspectives, setting the tone for a lighthearted exploration of relationships and society. The opening of "Cap'n Eri" introduces readers to Captain Eri and his comrades engaged in a playful yet philosophical discussion about boots, companionship, and the responsibilities of their bachelor lives. As they discuss various topics, from a wandering cat named Lorenzo to potential housekeepers, their banter reflects a blend of camaraderie and comic relief. The trio's conversation quickly turns to the more serious matter of marriage, specifically how one of them must wed for the benefit of the others. They decide to place an advertisement in a matrimonial journal, with Captain Jerry being chosen as the "sacrifice." This leads to humorous tension as they anticipate meeting their future bride$1 (Bthe narrative hints at misunderstandings and comedic mishaps ahead. (This is an automatically generated summary.)s
Release date is 2006-05-30
Produced by Donald Lainson; David Widger
Keywords: Ship captains -- Fiction; Massachusetts -- Fiction; Cape Cod (Mass.) -- Fiction; Housekeepers -- Fiction; Wives -- Fiction